Margret Dietrich: Zur Humanisierung des Lebens. Theater und Kunst. Ausgewählte Vorträge. Hrsg. V. Elisabeth Großegger, Andrea Sommer-Mathis und Dorothea Weber. Wien: Verlag der Österreichischen Akademie der Wissenschaften, 2000 - Eke, Norbert Otto (Germanistik)

Literaturunterricht in der Primar- und Orientierungsstufe - Büker, Petra (Grundzüge der Literaturdidaktik)

Composition of Efficient Nested BSP Algorithms: Minimum Spanning Tree Computation as an Instructive Example - Bonorden, Olaf; Meyer auf der Heide, Friedhelm; Wanka, Rolf (Int. Conf. on Parallel and Distributed Processing Techniques and Applications (PDPTA))

Any Load-Balancing Regimen for Evolving Tree Computations on Circulant Graphs Is Asymptotically Optimal - Wanka, Rolf (Proc. Workshop on Graph-Theoretic Concepts in Computer Science (WG))

Realtime Navigation in Highly Complex 3D-Scenes Using JPEG Compression - Klein, Jan; Krokowski, Jens; Cuntz, Nicolas (Proc. of 4. GI-Informatiktage)
We present a new and easy to use framework for navigating through scenes of arbitrary complexity and topology. In the preprocessing, images for discrete viewpoints and viewing directions are rendered and stored on an external volume. During navigation each image can be displayed within a very short time by loading it from the volume. For acceleration, our prefetching strategy loads possibly needed images for the next few frames if the viewer takes a break. The measurements show that we achieve interactive frame rates, whereby the difference between the minimal and maximal display time is very small. Our system works well with scenes modelled by polygons, but also digital photos can easily be used for describing a 3D scene.

Fremdverstehensförderung im Rahmen interkulturellen literarischen Lernens- zwei Fallstudien zur Rezeptionsforschung in der Grundschule. Kolloquiumsvortrag im Fach Germanistik der Universität Essen - Büker, Petra
Juli 2002

Reconfigurable Hardware in Wearable Computing Nodes - Plessl, Christian; Enzler, Rolf; Walder, Herbert; Beutel, Jan; Platzner, Marco; Thiele, Lothar (Proc. Int. Symp. on Wearable Computers (ISWC))
Wearable computers are embedded into the mobile environment of the human body. A design challenge for wearable systems is to combine the high performance required for tasks such as video decoding with low energy consumption required to maximize battery runtimes and the flexibility demanded by the dynamics of the environment and the applications. In this paper, we demonstrate that reconfigurable hardware technology is able to answer this challenge. We present the concept and the prototype implementation of an autonomous wearable unit with reconfigurable modules (WURM). We discuss two experiments that show the uses of reconfigurable hardware in WURM: ASICs-on-demand and adaptive interfaces. Finally, we develop and evaluate task placement techniques used in the operating system layer of WURM.
Keywords: wearable computing

Partially Reconfigurable Cores for Xilinx Virtex - Dyer, Matthias; Plessl, Christian; Platzner, Marco (Proc. Int. Conf. on Field Programmable Logic and Applications (FPL))
Recent generations of high-density and high-speed FPGAs provide a sufficient capacity for implementing complete configurable systems on a chip (CSoCs). Hybrid CPUs that combine standard CPU cores with reconfigurable coprocessors are an important subclass of CSoCs. With partially reconfigurable FPGAs, coprocessors can be loaded on demand while the CPU remains running. However, the lack of high-level design tools for partial reconfiguration makes practical implementations a challenging task. In this paper, we introduce a design flow to implement hybrid processors on Xilinx Virtex. The design flow is based on two techniques, virtual sockets and feed-through components, and can efficiently generate partial configurations from industry-quality cores. We discuss the design flow and present a fully operational audio streaming prototype to demonstrate its feasibility.
Keywords: partial reconfiguration

Custom Computing Machines for the Set Covering Problem - Plessl, Christian; Platzner, Marco (Proc. Int. Symp. on Field-Programmable Custom Computing Machines (FCCM))
We present instance-specific custom computing machines for the set covering problem. Four accelerator architectures are developed that implement branch & bound in 3-valued logic and many of the deduction techniques found in software solvers. We use set covering benchmarks from two-level logic minimization and Steiner triple systems to derive and discuss experimental results. The resulting raw speedups are in the order of four magnitudes on average. Finally, we propose a hybrid solver architecture that combines the raw speed of instance-specific reconfigurable hardware with flexible bounding schemes implemented in software.

Performance Evaluation, Analysis and Optimization - P. Miller, Barton; Labarta, Jesús; Schintke, Florian; Simon, Jens (Proc. European Conf. on Parallel Processing (Euro-Par))

Formal Description of a Distributed Location Service for Mobile Ad Hoc Networks - Benczúr, András; Glässer, Uwe; Lukovszki, Tamás (Proc. of 10th International Workshop on Abstract State Machines, LNCS)
We define here a distributed abstract state machine (DASM) [7] of the network or routing layer of mobile ad hoc networks [13]. Such networks re- quire routing strategies substantially different from those used in static commu- nication networks, since storing and updating large routing tables at mobile hosts would congest the network with administration packets very fast. In [1], the hypercubic location service is presented, which considers a very strong definition of fault-tolerance thereby improving state-of-the-art ad hoc routing protocols in several respects. Our goal in modeling the protocols for the distrib- uted location service and the position based routing is twofold. First, we support the definition and validation of wireless communication protocols and imple- mentations based thereon. Second, we feel that the abstract computation model naturally reflects the layering principle of communication architectures in com- bination with an uncompromisingly local view of the application domain. Thus we can identify fundamental semantic concepts, such as concurrency, reactivity and asynchronism, directly with the related concepts as imposed by the given application context.

Distributed Maintenance of Resource Efficient Wireless Network Topologies - Grünewald, Matthias; Lukovszki, Tamás; Schindelhauer, Christian; Volbert, Klaus (Proceedings of the 8th International Euro-Par Conference)

Eine Analysemethode zur Beurteilung der Funktionssicherheit von gemischt analog-digitalen Schaltungen - Wagenblaßt, Dieter

Leistungsbewertung eingebetteter Neurocomputersysteme - Porrmann, Mario

Methodik zum Aufbau von Informationsmodellen für Electronic Business in der Produktentwicklung - Seifert, Lars

Methode zur Modellierung, Kontrolle und Steuerung von Produktstrategien - Soetebeer, Martin

1. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung

Methode zur Konzipierung mechatronischer Systeme - Flath, Martin

Methoden zur Suche und Informationsbereitstellung von Lösungselementen für die Entwicklung mechatronischer Systeme - Avenarius, Joachim

Eine simulationsgestützte Methode für die optimale Budgetentscheidung im Kundenbindungsmanagement - Helmke, Stefan

Rechnerinterne Repräsentation von informationsverarbeitenden Lösungselementen für die verteilte kooperative Produktentwicklung in der Mechatronik - Czubayko, Roland

Anwendung mengenorientierter numerischer Methoden zur Analyse nichtlinearer dynamischer Systeme am Beispiel der Spurführungsdynamik von Schienenfahrzeugen - Goldschmidt, Stefan

Towards Device Driver Synthesis - Lehmann, Thomas; Winter, K.

Issueorientierte Frühaufklärung - Härtel, Wulf

Das Lebensarbeitszeitkonzept als Alternative zur Mehrarbeitszeitzuschlagslösung - Betz, Stefan (Zeitschrift für Planung)

Kontrollsystem - Betz, Stefan (Handwörterbuch Unternehmensrechnung und Controlling)

In-Situ Determination of the Charging of Nanometer and Submicron Particles at High Temperatures - Schiel, Annette; Weber, Alfred P.; Kasper, Gerhard; Schmid, Hans-Joachim (Particle & Particle Systems Characterization)
Thermal charging of submicron and nanometer particles has been studied for model aerosols of TiO2 and SiO2 as well as Al-Si (aluminosilicate) at 1 000 °C with a new quasi in-situ technique. The size dependence of the particle separation efficiency for electrostatic precipitation was determined. The charging state of the particles was obtained from evaluating the global Deutsch number for precipitation in an electric field applied to a laminar flow based on particle trajectory considerations.

In-Situ Measurement of Local Particle Flux Densities in a Complex Two-Phase Flow - Schmid, Hans-Joachim; Veith, Susanne; Umhauer, Heinz (Particle & Particle Systems Characterization)
An optical measuring technique is presented allowing the exact in-situ measurement of local particle flux densities in a confined channel flow by counting single particles penetrating an optically well defined measuring volume. This enables a precise flux determination up to the direct vicinity of planar walls. The measurement set-up and its calibration as well as the whole test facility are described in detail. This measurement technique is used to study the particle transport in electrostatic precipitators. Exemplarily, results of particle flux profiles as well as precipitation, as gained from balances of parts of the precipitator channel, are presented. Furthermore, the possibility to determine particle velocity fluctuations is demonstrated.

Trennprozesse: Abschnitt 7.5.3 - Schmid, Hans-Joachim (Handbuch der Mechanischen Verfahrenstechnik)
Summary Elektrische Staubabscheidung Wirkprinzip Mikroprozesse und Grundvorgänge Sekundäreinflüsse auf die Partikelabscheidung Wichtige Bestandteile und verschiedene Bauformen Auslegung von Abscheidern

A simulation environment for ad hoc networks using sector subdivision - Volbert, Klaus (Proceedings 10th Euromicro Workshop on Parallel, Distributed and Network-based Processing)

Individuelle und schulische Bedingungsfaktoren für Argumentationen und Beweise im Mathematikunterricht - Reiss, Kristina; Hellmich, Frank; Thomas, Joachim (Zeitschrift für Pädagogik)

Materialgebundene versus computerunterstützte Förderung räumlicher Kompetenzen in der Grundschule - Hellmich, Frank; Hartmann, Jens (Beiträge zum Mathematikunterricht 2002)

Bedingungen für das Argumentieren und Begründen im Geometrieunterricht der Sekundarstufe I - Hellmich, Frank; Hartmann, Jens; Reiss , Kristina (Beiträge zum Mathematikunterricht 2002)

Reasoning and proof in geometry: Prerequisites of knowledge acquisition in secondary school students - Reiss, Kristina; Hellmich, Frank; Reiss, Matthias (Proceedings of the 26th Conference of the International Group for the Psychology of Mathematics Education)

Aspekte einer Förderung räumlicher Kompetenzen im Geometrieunterricht. Ergebnisse einer Trainingsstudie mit Sonderschülerinnen und -schülern - Hellmich, Frank; Hartmann, Jens (Zentralblatt für Didaktik der Mathematik)

Begründen und Beweisen in der Geometrie. Bedingungen des Wissensaufbaus bei Schülerinnen und Schülern der Sekundarstufe. Ergebnisbericht an die DFG - Hellmich, Frank; Reiss, Kristina; Thomas, J

Relating State-based and Behaviour-oriented Subtyping - Wehrheim, Heike (Nord. J. Comput.)

Specification and Inheritance in CSP-OZ - Olderog, Ernst-Rüdiger; Wehrheim, Heike (Formal Methods for Components and Objects, First International Symposium, FMCO 2002, Leiden, The Netherlands, November 5-8, 2002, Revised Lectures)

Checking Behavioural Subtypes via Refinement - Wehrheim, Heike (Formal Methods for Open Object-Based Distributed Systems V, IFIP {TC6/WG6.1} Fifth International Conference on Formal Methods for Open Object-Based Distributed Systems {(FMOODS} 2002), March 20-22, 2002, Enschede, The Netherlands)

Kompetenzfördernde Arbeitsbedingungen - Harteis, Christian

Selbstgesteuertes Lernen in internetbasierten Weiterbildungsveranstaltungen - Gruber, Hans; Festner, Dagmar; Harteis, Christian; Meier, Bettina; Meling, Patrick; Stamouli, Elena; Winkler, Christiane (Selbstgesteuertes Lernen)

Anisotropic creep modeling based on elastic projection operators - Mahnken, Rolf (PAMM)

Priority encoding transmission - Albanese, Andres; Blömer, Johannes; Edmonds, Jeff; Luby, Michael; Sudan, Madhu (IEEE Transactions on Information Theory)

Priority encoding transmission - Albanese, A.; Blömer, Johannes; Edmonds, J.; Luby, M.; Sudan, M. (Proceedings 35th Annual Symposium on Foundations of Computer Science)

Catching‐Up, Falling Behind and the Role of FDI:A Model of Endogenous Growth and Development - Gries, Thomas (South African Journal of Economics)

Protein intake and urinary albumin excretion rates in the EURODIAB IDDM Complications Study - Toeller, M.; Buyken, Anette; Heitkamp, G.; Brämswig, S.; Mann, J.; Milne, R.; Gries, F. A.; Keen, H. (Diabetologia)

Relation of fibre intake to HbA 1c and the prevalence of severe ketoacidosis and severe hypoglycaemia - Buyken, Anette; Toeller, M.; Heitkamp, G.; Vitelli, F.; Stehle, P.; Scherbaum, W. A.; Fuller, J. H. (Diabetologia)

Carbohydrate sources and glycaemic control in Type 1 diabetes mellitus - Buyken, Anette; Toeller, M.; Heitkamp, G.; Irsigler, K.; Holler, C.; Santeusanio, F.; Stehle, P.; Fuller, J. H.; Group, the Eurodiab Iddm Complications Stu (Diabetic Medicine)

The Impact of Dietary Fat Composition on Serum Leptin Concentrations in Healthy Nonobese Men and Women - Kratz, Mario; von Eckardstein, Arnold; Fobker, Manfred; Buyken, Anette; Posny, Nicole; Schulte, Helmut; Assmann, Gerd; Wahrburg, Ursel (The Journal of Clinical Endocrinology & Metabolism)

Protein intake - new evidence for its role in diabetic nephropathy - Toeller, M; Buyken, Anette (Nephrology Dialysis Transplantation)